Synthesis and Characterization of Polyhydroxyethyl-Acrylate and Polyhydroxyethylmethacrylate Gel Dosimeters - Raba’eh, Khalid Ahmed Majali (2007)
Polymer gel dosimeters in conjunction with the nuclear magnetic resonance imaging (MRI) are potentially used for verification of complex dose distributions in three dimensions (3D) for radiotherapy treatment planning. The radiation-induced polymerization of hydroxyethylacrylate (HEA) and hydroxyethylmethacrylate (HEMA) polymer gel dosimeters has been studied using Raman spectroscopy, nuclear magnetic resonance (NMR) and MRI scanner. The HEA polymer gels were synthesized from 2-hydroxyethylacrylate (HEA) monomer (2 to 5% w/w), N,N’-methylene-bis-acrylamide (BIS) cross-linker (2 to 5% w/w), gelatin (3 and 5%) and de-ionized water in oxygen free environment. The HEMA polymer gels were synthesized from 2-hydroxyethylmethacrylate (HEMA) monomer (2 to 5% w/w), BIS (2 to 5% w/w), 5% gelatin and de-ionized water. The dosimeters were irradiated with 60Co teletherapy γ-ray source at a constant dose rate of 0.43 Gy/min, receiving doses up to 20 Gy for a single point dose measurement and up to 30 Gy for 3D dose distributions scanning. Raman spectroscopy was used to investigate directly the degree of radiation-induced polymerization and the rate of elapsed polymerization, targeting the COO stretching Raman shift at vibrational band of 1415 cm-1 assigned for HEA polymer gels and the OH stretching Raman shift at vibrational band of 3358 cm-1 assigned for HEMA polymer gels. The Raman intensity y corresponding to the amount of polymerization in both HEA and HEMA polymer gels increases with absorbed dose D in the dose range between 0 and 20 Gy and follows mono-exponential equation given as . The rate of elapsed polymerization in HEA and HEMA polymer gels decreases with absorbed dose in the dose range between 0 and 20 Gy and follows exponential equation given as )1(0/0DDeAyy−−+=0/0DDeDAdtdy−κ=. The dose sensitivity, D0 of polymerization and the half dose, D1/2 of the rate of elapsed polymerization in HEA and HEMA polymer gels increase strongly with increasing the cross-linker concentration than that of the monomer concentration where the dose correlation factor for the cross-linker is always greater than the dose correlation factor for the monomer. At 3% gelatin the D0 and D1/2 values of the HEA polymer gels always greater than at 5% gelatin, indicating that the polymerization and the rate of elapsed polymerization of HEA polymer gels increases with decreasing the amount of gelatin. The consumption of co-monomer in HEA and HEMA polymer gels decreases mono-exponentially with absorbed dose in the dose ranges between 0 and 20 Gy and it follows mono-exponential equation of the form()0/01DDeAyy−−−=. The result shows that the cross-linker consumption increases more significantly with absorbed dose than the monomer consumption. The nuclear magnetic resonance (NMR) spin–spin relaxation rate, R2 for water proton surrounding the polymer formation has been used to investigate indirectly the degree of polymerization and the rate of elapsed polymerization of HEA and HEMA polymer gels. The dose response of the change in relaxation rate, ΔR2 is also mono-exponential function and for the rate of elapsed polymerization it is normal exponential function. The dose sensitivity, D0 for the change in relaxation rate ΔR2 and the half dose, D1/2 for the rate of elapsed polymerization of HEA and HEMA polymer gels have produced results of similar trend to that of Raman spectroscopy method. The radiological film obtained from the clinical MRI scans of polymer gel phantom to simulate radiotherapy treatment planning was analyzed using a densitometer. The optical density of the polymer gels was found to increase with the increase of absorbed dose and decreases with the increase of depth inside the phantom. The dose-depth map for HEA polymer gels was derived for different concentrations of HEA and BIS co-monomers. The results suggest that for a clinical radiotherapy treatment planning the dose correction for tumour deep within the body should be implemented with knowledge of the amount of applied dose, tumour volume, skin to tumour distance, and tissue equivalent nature of the body. The percentage of depth dose was also evaluated which leads to a good agreement with the ionization chamber measurements. The indirect measurements of HEA and HEMA polymer gels using NMR have shown more dose sensitivity than that for direct measurements using Raman spectroscopy. In general the dose sensitivity and half dose of HEA polymer gels are grater than that for HEMA, indicating that the HEA polymer gels are more radiosensitive than that of HEMA polymer gels at a given dose. The dose-depth map has been achieved using HEA polymer gels in conjunction with MRI scanning which led to introduce a fit equation between dose and depth inside HEA polymer gels.